2012
DOI: 10.1111/j.1464-410x.2011.10874.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathology‐based risk stratification of muscle‐invasive bladder cancer patients undergoing cystectomy for persistent disease after induction chemoradiotherapy in bladder‐sparing approaches

Abstract: In CRT-based bladder-sparing approaches, patients with a clinical non-CR after induction CRT can be stratified into low- and high-risk groups for death from cancer based on pathology of cystectomy specimens. Patients at high risk are potential candidates for intensive adjuvant therapy including clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…38 Among patients who had undergone salvage cystectomy for clinical residual disease after induction CRT, CSS was favorable in cases of organ-confined disease (ՅpT2pN0; 5-year CSS rate, 85%), but quite poor when extravesical disease was present (ՆpT3 or pN+, 20%). 46 …”
Section: Prognostic Factors In Patients Treated With Trimodality Therapymentioning
confidence: 99%
“…38 Among patients who had undergone salvage cystectomy for clinical residual disease after induction CRT, CSS was favorable in cases of organ-confined disease (ՅpT2pN0; 5-year CSS rate, 85%), but quite poor when extravesical disease was present (ՆpT3 or pN+, 20%). 46 …”
Section: Prognostic Factors In Patients Treated With Trimodality Therapymentioning
confidence: 99%
“…High-grade and muscle-invasive bladder cancers treated with RC have varied prognoses [6,7]. In recent years, several "variant" morphologies have been described, and most were recognized in the 2004 World Health Organization Classification [8].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that variant pathologic tumors are aggressive, a fact that has significant prognostic implications. In view of this factor, early recognition may require novel therapeutic interventions, such as the administration of a therapy distinctive from that used for conventional invasive UC [6]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…propose that patients proven to be non‐CR after induction CRT in bladder‐sparing approaches be grouped into different risk groups for death based on conventional pathology of cystectomy specimens . In patients who underwent radical surgery, pT3–4a (HR 8.3 vs pT0–2, P < 0.001) and pN+ (HR 3.0 vs pN0, P = 0.037) were found to be independent risk variables among other factors including pT stage, lymph node yield at surgery, pN stage and lymphovascular invasion . Patients proven to be non‐CR were grouped by the risk factors into low‐ (pT0–2pN0, 5‐year CSS rate 85%) and high‐risk (pT3–4a or pN+, 5‐year CSS rate 20%) groups …”
Section: Principles Of Bladder Preservationmentioning
confidence: 99%